Proceedings of the 55th Annual Meeting of the Association For Computational Linguistics (Volume 2: Short Papers) 2017
DOI: 10.18653/v1/p17-2034
|View full text |Cite
|
Sign up to set email alerts
|

A Corpus of Natural Language for Visual Reasoning

Abstract: We present a new visual reasoning language dataset, containing 92,244 pairs of examples of natural statements grounded in synthetic images with 3,962 unique sentences. We describe a method of crowdsourcing linguistically-diverse data, and present an analysis of our data. The data demonstrates a broad set of linguistic phenomena, requiring visual and set-theoretic reasoning. We experiment with various models, and show the data presents a strong challenge for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
157
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(162 citation statements)
references
References 21 publications
1
157
0
Order By: Relevance
“…To elicit this property, we sampled all attributes of the entities uniformly at random, with the only restriction that the entities cannot be too close to each other. As the previous work with similar idea confirmed (Suhr et al 2017), we found rich varieties of linguistic phenomena, including cardinalities ("three gray dots"), existentials ("There is another small dark .."), universals ("all of the other dots are larger"), coordinations and negations ("further to the right and not as far down").…”
Section: Dataset Collectionsupporting
confidence: 88%
See 4 more Smart Citations
“…To elicit this property, we sampled all attributes of the entities uniformly at random, with the only restriction that the entities cannot be too close to each other. As the previous work with similar idea confirmed (Suhr et al 2017), we found rich varieties of linguistic phenomena, including cardinalities ("three gray dots"), existentials ("There is another small dark .."), universals ("all of the other dots are larger"), coordinations and negations ("further to the right and not as far down").…”
Section: Dataset Collectionsupporting
confidence: 88%
“…• In a categorical context (Bordes and Weston 2016;He et al 2017;Lewis et al 2017), information can be expressed by symbolic natural language without ambiguity. For example, there could be little ambiguity in describing categorical properties, such as discrete color (red, blue and yellow).…”
Section: A's View B's Viewmentioning
confidence: 99%
See 3 more Smart Citations